2022
DOI: 10.7759/cureus.26741
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as an Independent Risk Factor for In-Patient Mortality in Hospitalized COVID-19 Patients: A Multicenter Study

Abstract: Despite the lack of direct evidence that hypertension increases the likelihood of new infections, hypertension is known to be the most common comorbid condition in COVID-19 patients and also a major risk factor for severe COVID-19 infection. The literature review suggests that data is heterogeneous in terms of the association of hypertension with mortality. Hence, it remains a topic of interest whether hypertension is associated with COVID-19 disease severity and mortality. Herein, we perform a multicenter ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A multicenter study done by Mirza et al on the effect of lone hypertension for severe COVID-19 status revealed that hypertension was not an independent risk factor for in-hospital death after being adjusted for other comorbidities in COVID-19 patients [23]. Although it is hard to tell, previous studies still unanswered whether the stage of hypertension or diabetes with each case is controlled or uncontrolled, or whether more than one comorbidity, stage of the disease, or its complications lead to severe condition of COVID-19 [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study done by Mirza et al on the effect of lone hypertension for severe COVID-19 status revealed that hypertension was not an independent risk factor for in-hospital death after being adjusted for other comorbidities in COVID-19 patients [23]. Although it is hard to tell, previous studies still unanswered whether the stage of hypertension or diabetes with each case is controlled or uncontrolled, or whether more than one comorbidity, stage of the disease, or its complications lead to severe condition of COVID-19 [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of patients with HTN died, and the P -value of 0.071 indicates a potential trend towards a difference in mortality, but it is not statistically significant. The literature review found that the association between hypertension and mortality is heterogeneous 35 , 36 . More research is needed to determine the exact role of hypertension in COVID-19 disease severity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing and chronic comorbidities have been identified as key risk factors for SARS-CoV-2 infection [ 7 ]. Furthermore, diabetes mellitus (DM), hypertension, obesity and cardiovascular diseases have been identified as the most predominant comorbidities among individuals infected with SARS-CoV-2 [ 7 , 8 , 9 , 10 ]. It has been shown that these comorbidities are risk factors for poor outcome and mortality in individuals infected with SARS-CoV-2 [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, diabetes mellitus (DM), hypertension, obesity and cardiovascular diseases have been identified as the most predominant comorbidities among individuals infected with SARS-CoV-2 [ 7 , 8 , 9 , 10 ]. It has been shown that these comorbidities are risk factors for poor outcome and mortality in individuals infected with SARS-CoV-2 [ 8 , 10 , 11 ]. The mechanism in which these comorbidities worsen COVID-19 outcomes may involve immune and inflammatory responses, modulated by hyperglycaemia and the renin–angiotensin system [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%